ARP/wARP's model-building algorithms. I. The main chain - Morris, Richard J.; Perrakis, Anastassis; Lamzin, Victor S. (Acta crystallographica. Section D, Biological crystallography., 2002)
Algorithms underlying the automatic model‐building functionality of the ARP/wARP software suite are presented. Finding the most likely set of Cα atoms from a given set of atoms is formulated as a constrained integer programming problem. The objective function is a density‐weighted score for the match between observed and expected chain conformation. Graph‐search algorithms are presented that find solutions to this problem in an efficient manner.